Fabrication of dense Ce0.9Mg0.1P2O7-PmOn composites by microwave heating for application as electrolyte in intermediate-temperature fuel cells - Singh B.; Devi N.; Mathur L.; Singh R.K.; Bhardwaj A.; Song S.-J.; Henkensmeier D. (My University, 2025)
In the present work, we report a method of fabrication of dense 10 mol% Mg2+-doped cerium pyrophosphate-phosphate (Ce0.9Mg0.1P2O7-PmOn; CMP-P) composites by microwave heat-treatment of the preformed Ce0.9Mg0.1P2O7 substrates in the presence of phosphoric acid. The composite was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and electrochemical impedance spectroscopy (EIS). The microwave heating at 375 °C for 5 min resulted in the formation of dense CMP-P composites which retained most of the pyrophosphate phase. The electrical conductivity was extracted from the EIS data and for the CMP-P composite prepared by H3PO4 loading for 10 h and microwave heat-treatment for 5 min it was found to be >10−2 S m−1 in 100–250 °C range with a maximum of 0.062 S cm−1 at 190 °C, which was significant for its application as electrolyte in intermediate temperature fuel cells. © 2018 Elsevier Ltd and Techna Group S.r.l.